2018
DOI: 10.1093/pm/pnx294
|View full text |Cite|
|
Sign up to set email alerts
|

Swimming Training Attenuates Allodynia and Hyperalgesia Induced by Peripheral Nerve Injury in an Adult Male Rat Neuropathic Model: Effects on Irisin and GAD65

Abstract: Our findings showed that four weeks of swimming training produce beneficial rehabilitative effects on neuropathic pain symptoms. The analgesic effect of swimming training is partially related to the increase of GAD65. The beneficial role of irisin in neuropathic pain will require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…The two species of rats in the included studies were Sprague–Dawley (78.6%) and Wistar rats (21.4%). Only one study (22) (7.1%) used female rats, and 13 studies (1221, 2325) (92.9%) used male rats in their experiments. The age of the rats was mentioned in 3 studies (17, 18, 22), which ranged from 6 weeks old to 12 weeks old, and 4 articles (13, 2325) described as adult rats.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two species of rats in the included studies were Sprague–Dawley (78.6%) and Wistar rats (21.4%). Only one study (22) (7.1%) used female rats, and 13 studies (1221, 2325) (92.9%) used male rats in their experiments. The age of the rats was mentioned in 3 studies (17, 18, 22), which ranged from 6 weeks old to 12 weeks old, and 4 articles (13, 2325) described as adult rats.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study (22) (7.1%) used female rats, and 13 studies (1221, 2325) (92.9%) used male rats in their experiments. The age of the rats was mentioned in 3 studies (17, 18, 22), which ranged from 6 weeks old to 12 weeks old, and 4 articles (13, 2325) described as adult rats. A total of 12 studies (1217, 1921, 2325) described the weight of rats, which ranged from 180 to 380 g. Three pain models were reported in the different studies, which included SNL (21.4%), CCI (50%), and diabetic neuropathy (28.6%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, irisin expression is enriched in GABAergic cells [ 65 ], which release gamma-aminobutyric acid (GABA), a major inhibitory neurotransmitter, which inhibits neuropathic pain [ 66 , 67 , 68 ]. Exercise increases circulating GABA [ 69 ] and prevents a reduction in the level of glutamate decarboxylase 65, which catalyzes the decarboxylation of glutamate to GABA in the nervous system [ 35 ]. Although several studies have revealed that exercise promotes GABA signaling [ 70 , 71 , 72 ], how irisin regulates the GABA pathway remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise and physical therapy alleviate chronic neuropathic pain by modulating neuroinflammation [ 29 , 30 , 31 , 32 , 33 ]. Irisin has also been suggested to alleviate pain sensitization [ 34 , 35 ] and possess diagnostic value for pain symptoms [ 36 , 37 ]. However, its role in burn-induced neuropathy remains unclear.…”
Section: Introductionmentioning
confidence: 99%